ANALISIS KESALAHAN EJAAN KARANGAN PESERTA DIDIK KELAS VIII A SMPN 35 SURABAYA - Naimatul Hidayah; Rahayu Pujiastuti (Universitas PGRI Adi Buana Surabaya, 2020)
This study aimed to describe (1) the error of use letters in the text on the students of SMPN 35 Surabaya, (2) the error of use punctuation in the text on students of SMPN 35 Surabaya.The research that used in this research is qualitative research. The data of this research are that words, sentences and paragraphs which is include the errors of use letters and the errors of punctuation in the text on students of SMPN 35 Surabaya in the lesson year 2017. The source data is the assignment text to the students of SMPN 35 Surabaya with total is 16 posts. It is an exposition. The data collection of this research is done through documentation technique. The steps of analysis data is classifying, coding, interpreting and concluding. Based on the result of this research and discussion concluded that the spelling error on the students’ exposition text class VIII A of SMPN 35 Surabay, are (1) the error of use letters that occur in capital letters and italics and (2) errors in the use of punctuation that occurs on the dot, commas, quotes, and hyphens.